The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adfm.202108203
|View full text |Cite
|
Sign up to set email alerts
|

Stable Cycling of All‐Solid‐State Batteries with Sacrificial Cathode and Lithium‐Free Indium Layer

Abstract: All-solid-state batteries (ASSBs) comprising solidified cathodes, electrolytes, and Li-metal anodes have attracted notable attention as promising future batteries for electric vehicles owing to their exceptional stability and expectation of achieving high energy density. However, its permanent operation has been hindered by Li dendrite growth, chemo-mechanical degradation, and interfacial instability, leading to Li exhaustion, increased resistance, and internal short-circuiting. Herein, for the first time, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…This has been demonstrated as an effective strategy for fabricating practical Li metal full cells [ 39 43 ]. However, the currently reported sacrificial agents, such as Li 2 O and Li 3 N, are air-sensitive and not suitable for actual productions [ 44 , 45 ]. An ideal cathode prelithiation reagent should possess excellent air stability, high charge specific capacity, low charge/discharge reversibility, reasonable operating voltage range and harmless decomposition products.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated as an effective strategy for fabricating practical Li metal full cells [ 39 43 ]. However, the currently reported sacrificial agents, such as Li 2 O and Li 3 N, are air-sensitive and not suitable for actual productions [ 44 , 45 ]. An ideal cathode prelithiation reagent should possess excellent air stability, high charge specific capacity, low charge/discharge reversibility, reasonable operating voltage range and harmless decomposition products.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the concept of prelithiation strategies, Park et al first reported lithium nitride (Li 3 N) as the sacrificial cathode material to assemble all-solid-state batteries with Li-free In layer (Figure 4d). [62] In this study, Li 6 PS 5 Cl was used as solid electrolyte due to its high room-temperature ionic conductivity (10 À2 À10 À3 S cm À1 ). [63] It can be observed from the charging curve that a voltage plateau appeared at 2.4 V (%3.0 V vs Li/Li þ ), which was ascribed to the decomposition of Li 3 N (Figure 4e).…”
Section: The Solid Electrolytementioning
confidence: 99%
“…Combined, the B doping and the B coating protect the interior and exterior of a Ni-rich layered cathode to afford an ASSB that demonstrates superior long-term cycling stability. Finally, Figure S9 compares the cycling performance of the ASSB featuring a BCD-NCM90 cathode with those of recently reported ASSBs. None of the reported ASSBs features a Ni-rich layered cathode with Ni contents ≥0.9; as a result, the ASSB featuring a BCD-NCM90 cathode and Li 6 PS 5 Cl SE demonstrates a much higher specific discharge capacity. The ASSB featuring a BCD-NCM90 cathode also outperforms other reported ASSBs in terms of areal capacity without compromising cycling stability.…”
mentioning
confidence: 96%